A trianoni békediktátum történetének új kutatási irányai: ideiglenes államterek a magyar királyság területén. 1. Elméleti alapvetés: NEW RESEARCH DIRECTIONS IN THE HISTORY OF THE TREATY OF TRIANON: PROVISIONAL STATE FORMATIONS ON THE TERRITORY OF THE KINGDOM OF HUNGARY. 1. THEORETICAL FOUNDATION - Gulyás, László (Közép-Európai Közlemények, 2020)
On the centenary of Trianon some historians boldly claimed that we know all about the history of the peace treaty. The author of the present paper thinks that this claim is false. Thanks to the anniversary many new research topics have emerged. One of them is the problem of provisional state formations. During the fall of 1918 a huge wave self-determination swept through Central Europe prompted by Wilson’s Fourteen Points. Almost every nation living in the vast region stretching from the Baltic Sea to the Aegean Sea has declared its sovereignty. In the Austro-Hungarian Monarchy 11 nations lived, so it was not surprising that on the territories of the Austrian Empire and the Kingdom of Hungary dozens of popular assemblies have proclaimed the self-determination of various nations, and the formation of new states. Some of the states thus formed have proven to be short-lived: some of them lasted for only a single day, but even the longest lasting one existed just for a few years. The Hungarian Historical Studies uses the technical term „provisional state formations” on these failed attempts at state forming, while in his 2018 study on the Republic of Heinzenland Ferenc Szávai used the expression „ephemeral republic” on them.[i] The current paper seeks an answer to the following methodological question: how should the comparative history of provisional state formations be written.